Pelatihan Bimbingan Konseling Pada Kader PIK M di Kampus UIAD Sinjai Dalam Meningkatkan Rasa Percaya Diri - Suriyati; Suriati; Rahmatullah; Mutmainnah; Riska (Fakultas Ushuluddin dan Komunikasi Islam, 2024)
Self-confidence is a positive evaluation of oneself, including attitudes towards personal beliefs and abilities in facing life as well as a comprehensive view of oneself. Self-confidence shows a positive assessment of an individual's competence or skills. Therefore, holding a counseling guidance training for PIK M cadres to increase self-confidence. The objectives to be achieved in this research are: (1) increase cadres' understanding of self-confidence, (2) cadres can have self-confidence, (3) can solve problems experienced by cadres in terms of lack of self-confidence through counseling guidance. Researchers use the Service learning method with three stages: planning stage, implementation stage, reflection stage. The solution given is to give appreciation to the cadres, suggesting that they continue to practice, increase their reading and vocabulary. The results of this training show that the implementation was carried out from start to finish, cadres already understood what self-confidence is like, and there were several cadres who were able to prove their self-confidence by appearing to speak in public